Fast reconfiguration algorithms for time, space, and wavelength dilated optical Benes networks - Lu, Enyue; Zheng, S. Q. (International journal of parallel, emergent and distributed systems, 2007)
Benes networks are rearrangeable nonblocking networks and are among the most efficient switching architectures in terms of the number of switching elements (SEs) used. In optical Benes networks, if two I/O connecting paths with the same (close) wavelength(s) share a common SE, crosstalk occurs. In order to reduce the crosstalk effect, three approaches, time, space and wavelength dilations have been proposed. In this paper, we present polylogarithmic-time reconfiguration algorithms for realizing any (partial) permutation in time, space and wavelength dilated optical Benes networks using a linear number of processors. Our algorithms are based on a logarithmic-time permutation decomposition algorithm and apply graph coloring techniques such as edge coloring, equitable coloring and vertex coloring.